2020
DOI: 10.1136/jitc-2020-001588
|View full text |Cite
|
Sign up to set email alerts
|

EBV-EBNA1 constructs an immunosuppressive microenvironment for nasopharyngeal carcinoma by promoting the chemoattraction of Treg cells

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is primarily caused by the Epstein-Barr virus (EBV) infection in NPC endemic areas. EBNA1 is an EBV-encoded nuclear antigen, which plays a critical role in the maintenance and replication of EBV genome. However, the mechanisms of EBNA1-promoted NPC immune escape are unknown. Regulatory T (Treg) cells are among the key regulators in restraining antitumor responses. However, the mechanisms of accumulation of Treg cells in NPC have not been defined. This study attempted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Type II latency is characterized by the expression of a set of latent genes in NPC, including Epstein-Barr nuclear antigen 1 (EBNA1), latent membrane protein 1 (LMP1), LMP2 and Epstein-Barr encoding region (EBER) RNAs (32,33). LMP1 and EBNA1 expressed by NPC cells are able to induce PD-L1 up-regulation via STAT3 and NF-kB signaling, Treg recruitment via CXCL12-CXCR4 chemotaxis, as well as expansion of myeloid-derived suppressor cells (MDSCs) (31,34,35). EBV can also infect B cells, however, the infiltrating B cells in the NPC microenvironment are uninfected, indicating that EBV infection on nasopharyngeal epithelial cells may occur prior to B-cell recruitment and accumulation (36).…”
Section: The Heterogenous Npc Microenvironment Shaped By Locoregional Lymphoid Infiltration Ebv Infection and Tumor-mediated Recruitmentmentioning
confidence: 99%
“…Type II latency is characterized by the expression of a set of latent genes in NPC, including Epstein-Barr nuclear antigen 1 (EBNA1), latent membrane protein 1 (LMP1), LMP2 and Epstein-Barr encoding region (EBER) RNAs (32,33). LMP1 and EBNA1 expressed by NPC cells are able to induce PD-L1 up-regulation via STAT3 and NF-kB signaling, Treg recruitment via CXCL12-CXCR4 chemotaxis, as well as expansion of myeloid-derived suppressor cells (MDSCs) (31,34,35). EBV can also infect B cells, however, the infiltrating B cells in the NPC microenvironment are uninfected, indicating that EBV infection on nasopharyngeal epithelial cells may occur prior to B-cell recruitment and accumulation (36).…”
Section: The Heterogenous Npc Microenvironment Shaped By Locoregional Lymphoid Infiltration Ebv Infection and Tumor-mediated Recruitmentmentioning
confidence: 99%
“…CXCR4 is highly expressed in various types of tumor cells and tissues, and can be involved in tumor growth, invasion, angiogenesis and metastasis, such as breast cancer, colorectal cancer, pancreatic cancer, etc. promote NPC immune escape [9]. In Xu's study, the results showed that in NPC, LMP1 affects cell motility and invasion by inducing CXCR4 [33].…”
Section: Discussionmentioning
confidence: 96%
“…Apart from LMP1, other EBV viral oncoproteins and miRNAs are also implicated in the shaping of TIME. In NPC cell lines, EBNA1 activates TGFb1-SMAD3 signaling and suppression of miR-200a, leading to increased CXCL12 expression and recruitment of CXCR4+ Tregs (121). EBNA1 also enhanced the production of CCL20, which is also important for Treg migration (122).Tumours with higher density of Treg infiltration correlate with EBNA1 expression and found to have a poorer survival.…”
Section: Shaping Of the Npc Time By Ebv Oncoproteins And Tumour-mediated Recruitmentmentioning
confidence: 99%
“…CAFs have been associated with EMT transition and metastasis (1,11,146), and can be found around tumour cell nests, with varying amounts in different NPCs (138,139). Again, LMP1 has been shown in vitro to facilitate transition normal fibroblasts (NF) to CAFs (121,147). Alpha smooth muscle actin (aSMA), an immune marker for CAFs, was found to be correlated with CD34, an indicator of neoangiogenesis (121,147).…”
Section: Other Cell Populations In Npc Timementioning
confidence: 99%
See 1 more Smart Citation